A PRESENTATION OF CREATED SOFTWARE AND OTHERS PLANS FOR A DESIGN OF WEB-BASED TRANING SUPPORT - BORZIKOVA, Jana (Trends in education, 2009)
The second article deals is described the created software for subject and there are presented other plans to assembling a dynamic parts, task generator, camera transmission of experiment, which using numerical methods. The aim is to created complete web-based learning support for a subject Applied mathematics.
Keywords: Blended Learning; VBA for Application library; Applied Mathematics